Analysis of the Impact of BOPO, FDR, NOM and NPF on ROA of Indonesian Sharia Commercial Banks Registered with the OJK - Dina Sentika; Eko Sujadi; Elex Sramigi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Return on Resources (ROA) is a marker used to evaluate the effectiveness of an organization in producing benefits utilizing the resources it possesses. The point of this examination is to distinguish factors that impact the degree of organization benefit. Specialists use organization size factors, BOPO, FDR, NOM, and NPF on ROA. The example in this study was 12 banks, and 15 banks had a populace since 3 banks were not deserving of examination in Sharia Business Banks enlisted with the OJK in the period 2019 - 2022. Signaling Theory and Agency Theory are utilized in this study. This examination classification incorporates quantitative strategies utilizing an acquainted methodology, the focal point of which is investigating the effect of at least two factors and utilizing auxiliary information. The tests in this examination are the Traditional Supposition test and Numerous Straight Relapse Test. The consequences of this exploration show that there is an impact between all free factors on the reliant variable, there are two factors that have a huge positive impact (FDR and NOM), and there are two factors that have a critical adverse impact (BOPO and NPF). It is hoped that the findings of this study will help banks manage the factors that affect their level of profitability in order to boost profitability. It is likewise trusted that this study can turn into a reference for lenders and borrowers to survey banking execution all the more effectively and give a premise to navigation. It is hoped that it will provide additional variables that influence bank profitability as a direction for future research.Return on Resources (ROA) is a marker used to evaluate the effectiveness of an organization in producing benefits utilizing the resources it possesses. The point of this examination is to distinguish factors that impact the degree of organization benefit. Specialists use organization size factors, BOPO, FDR, NOM, and NPF on ROA. The example in this study was 12 banks, and 15 banks had a populace since 3 banks were not deserving of examination in Sharia Business Banks enlisted with the OJK in the period 2019 - 2022. Signaling Theory and Agency Theory are utilized in this study. This examination classification incorporates quantitative strategies utilizing an acquainted methodology, the focal point of which is investigating the effect of at least two factors and utilizing auxiliary information. The tests in this examination are the Traditional Supposition test and Numerous Straight Relapse Test. The consequences of this exploration show that there is an impact between all free factors on the reliant variable, there are two factors that have a huge positive impact (FDR and NOM), and there are two factors that have a critical adverse impact (BOPO and NPF). It is hoped that the findings of this study will help banks manage the factors that affect their level of profitability in order to boost profitability. It is likewise trusted that this study can turn into a reference for lenders and borrowers to survey banking execution all the more effectively and give a premise to navigation. It is hoped that it will provide additional variables that influence bank profitability as a direction for future research.